Perioperative management of massive hemoptysis during flexible bronchoscopy : case report (2017)
Flexible bronchoscopy is a diagnostic or therapeutic procedure with a low incidence of complications (0.08–6.8%). Bleeding after transbronchial biopsy is a rare complication (0-2.8% of the cases), usually resulting in minor bleeding that resolves with loc